Effects of heat stress abatement on behavioral response in lactating dairy cows prior to and following an intramammary lipopolysaccharide infusion - T.N. Marins; R.M. Orellana Rivas; Y-C. Chen; V.H.L.R. Melo; Z. Wang; H. Liu; J. Gao; C.G. Savegnago; A.M. Roper; J.K. Bernard; P. Melendez; S. Tao (Journal of Dairy Science)
ABSTRACT: The assessment of animal behavior serves as a valuable approach to identify illness and animal responses to environmental stimuli. Both heat stress and mastitis are reported to affect the behavioral responses of dairy cattle. However, little is known about the effects of heat stress on the lactating cow's behavioral responses to mastitis. The aims of the current study were to evaluate the effects of deprivation of evaporative cooling on behavioral responses of lactating dairy cows before and following mammary inflammation induced by intramammary LPS (IM-LPS) infusion and to characterize the effect of deprivation of evaporative cooling on feed sorting in lactating dairy cows during summer. Multiparous mid-lactating Holstein dairy cows (n = 18, parity = 2.4 ± 0.6, DIM = 136 ± 61 d) were randomly assigned to: evaporatively cooled (CL, n = 9) or not cooled (NC, n = 9) for 36 d (average temperature-humidity index = 78.4). The evaporative cooling system included misters and fans. Misters were installed on the front face of each fan, which was placed over both feed bunk and freestalls. On d 30, the left rear quarters of a subset of cows (n = 14, 7 per treatment) were infused with a bolus of LPS (10 µg of Escherichia coli O111:B4 LPS). Feeding and resting behaviors were recorded throughout the experiment using automated sensor devices (NEDAP). Sorting activity based on particle size separation using a Penn State Particle Separator was assessed at d 3, 16, and 26 of the experiment. Before IM-LPS, NC cows had lower ruminating and eating time, and consequently greater inactive time compared with CL cows. Relative to CL cows, NC cows had reduced lying time, and greater standing and walking time. The NC cows also had greater standing bouts, only at the beginning of the experiment, relative to CL cows. Additionally, NC cows sorted more for long particles (NC: 99.4% vs. CL: 94.4%) and sorted against medium and short particles on d 3 of the experiment compared with CL cows. However, following IM-LPS, no significant differences in behavioral responses were observed between NC and CL cows. In conclusion, deprivation of evaporative cooling negatively affected the behavioral responses of lactating dairy cows during summer. Further, heat-stressed cows without evaporative cooling sorted more for long particles of the diet potentially as a response to cope with the reduced rumen pH. However, deprivation of evaporative cooling does not have a significant effect on the lactating cow's behavioral responses to LPS induced mammary inflammation.